2007
DOI: 10.1104/pp.107.096388
|View full text |Cite
|
Sign up to set email alerts
|

Increased Abundance of Proteins Involved in Phytosiderophore Production in Boron-Tolerant Barley

Abstract: Boron (B) phytotoxicity affects cereal-growing regions worldwide. Although B-tolerant barley (Hordeum vulgare) germplasm is available, molecules responsible for this tolerance mechanism have not been defined. We describe and use a new comparative proteomic technique, iTRAQ peptide tagging (iTRAQ), to compare the abundances of proteins from B-tolerant and -intolerant barley plants from a ‘Clipper’ × ‘Sahara’ doubled-haploid population selected on the basis of a presence or absence of two B-tolerance quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 42 publications
(51 reference statements)
0
38
0
2
Order By: Relevance
“…Currently, SILAC, iTRAQ, and iBAQ are considered to be among the most promising techniques for large-scale quantitative proteome analyses in plant biology (128,124). However, despite numerous advantages of quantitative shotgun proteomics, there are only a few reports that employed these techniques for analyses of metal toxicity-induced proteins in plants (80,129,130). iTRAQ was used by Patterson et al (129) for quantitative determination of proteins in two barley cultivars with different sensitivity to increased boron concentrations and the results obtained suggested that iTRAQ had a considerable potential for identifying and quantifying the expression of proteins in conjunction with bulked segregant analysis.…”
Section: Mass Spectrometry (Ms) Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, SILAC, iTRAQ, and iBAQ are considered to be among the most promising techniques for large-scale quantitative proteome analyses in plant biology (128,124). However, despite numerous advantages of quantitative shotgun proteomics, there are only a few reports that employed these techniques for analyses of metal toxicity-induced proteins in plants (80,129,130). iTRAQ was used by Patterson et al (129) for quantitative determination of proteins in two barley cultivars with different sensitivity to increased boron concentrations and the results obtained suggested that iTRAQ had a considerable potential for identifying and quantifying the expression of proteins in conjunction with bulked segregant analysis.…”
Section: Mass Spectrometry (Ms) Techniquesmentioning
confidence: 99%
“…In a comparative proteomic study of B-sensitive and B-tolerant barley exposed to increased B concentrations, Patterson et al (129) reported an enhanced abundance of enzymes phytosiderophores involved in production of proteins with a strong chelatin activity, which participate in iron uptake in B-tolerant barley.…”
Section: Current Trends In Proteomics Of Heavy Metal Toxicity In Plantsmentioning
confidence: 99%
“…Sea water contains 4.5-5 mg L −1 of B. It has also been reported that many cereal-growing regions of Australia, North Africa and Western Asia suffer from B toxicity (Patterson et al 2007). …”
Section: Boron Toxicitymentioning
confidence: 99%
“…However, B concentrations in their roots and shoots are not significantly different (Ochiai et al 2008). Boron-tolerant barley varieties have been reported to contain elevated levels of three enzymes involved in phytosiderophore production such as iron-deficiency sensitive proteins IDS2, IDS3 and a methyl thio-ribose kinase (Patterson et al 2007). There appears to be a potential link between Fe, B and the siderophore hydroxy mugineic acid.…”
Section: Crop Tolerance To Bmentioning
confidence: 99%
“…RuBisCObağlayıcı altbirim, RuBisCO büyük altbiriminin katlanması için gerekli bir proteindir (Boston et al 1996). RuBisCO aktivaz, RuBisCO'nun katalitik aktivitesini sağlamaktadır (Portis 2003 Patterson et al 2007;Zhen et al 2007;Führs et al 2008;Farinati et al 2009;Zhang et al 2009;Walliwalagedara et al 2010;Cai et al 2011 Metal stresine cevap olarak RuBisCO proteininin miktarındaki azalma birçok bitki türünde rapor edilmiştir (Hajduch et al 2001;Führs et al 2008;Kieffer et al 2009;Ahsan et al 2010;Zhao et al 2011). Bununla birlikte, RuBisCO alt birimlerindeki azalma Cd stresine maruz kalan hiperakümülatör Thlaspi caerulescens bitkilerinde de belirlenmiştir (Tuomainen et al 2006).…”
Section: Karbondioksit öZümlemesi Ve Fotosentez Ile İlişkili Proteinlerunclassified